Peripheral blood gene expression stratifies rate of progression to type 1 diabetes in autoantibody-positive children in the TEDDY study - Hee, Jia Yi; Abraham, Yann; Mehdi, Ahmed M.; Lê Cao, Kim-Anh; Thomas, Ranjeny (Frontiers in Immunology, 2025)
IntroductionIn type 1 diabetes, autoimmune destruction of pancreatic β cells results in insulin deficiency, leading to hyperglycemia. Islet autoantibodies, which precede autoimmune progression, usually develop years before diabetes onset, although some individuals develop diabetes without them. However, not all children who develop islet antibodies progress to diabetes, and they do not all progress at the same rate. Genomic markers may help identify high-risk children for early intervention.MethodsUsing gene expression profiles derived from peripheral blood mononuclear cells collected from 62 high-risk, islet autoantibody-positive children in the TEDDY cohort study, of whom 56 progressed to diabetes, we identified differentially expressed genes, pathways, and protein–protein interactions associated with progression from islet autoantibody seropositivity to the clinical onset of diabetes.ResultsAfter seroconversion, progressors were distinguished by a peripheral blood gene expression profile enriched for MHC class II-related functions and immune response pathways. Within protein– protein interaction (PPI) networks, we identified SMARCA4 as the central hub and found that its expression stratified progression to type 1 diabetes after seroconversion. Differentially expressed genes in the PPI networks were also highly connected to type 1 diabetes drug–gene targets, particularly JAK2.DiscussionThe enrichment of MHC class II-related functions and immune response pathways after seroconversion highlights immune activation in progressors, whose rate of progression could be stratified as fast or slow based on a 20-gene signature, which warrants confirmation in an independent cohort.